1994
DOI: 10.1055/s-2007-994598
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Adrenal Hemorrhage Associated with Fetal Distress, Subsequent Transient Neonatal Hypertension, and a Nonfunctioning Ipsilateral Kidney

Abstract: We present an unusual case of in utero adrenal hemorrhage associated with fetal distress. This case was further complicated by transient neonatal hypertension that resolved spontaneously and a nonfunctioning ipsilateral kidney. We discuss the possible underlying pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…In the four cases reported in the English-language literature, adrenal hemorrhage, partial or complete ipsilateral renal function loss and hypertension were observed, and hypertension was improved following the resolution of bleeding. [2][3][4] Sherer et al [2] presented a case with transient neonatal hypertension due to in utero adrenal hemorrhage. Sirota et al [3] reported a case of newborn with adrenal hemorrhage associated with transient compression of the kidney and hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the four cases reported in the English-language literature, adrenal hemorrhage, partial or complete ipsilateral renal function loss and hypertension were observed, and hypertension was improved following the resolution of bleeding. [2][3][4] Sherer et al [2] presented a case with transient neonatal hypertension due to in utero adrenal hemorrhage. Sirota et al [3] reported a case of newborn with adrenal hemorrhage associated with transient compression of the kidney and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of the our knowledge, it has been reported only in a few cases in the English-language literature. [2][3][4] Here, we present a newborn who had a history of birth trauma and adrenal hemorrhage, and consequently developed hypertension. Birth trauma is a complication that sometimes occurs despite good obstetric care due to difficult labor, abnormal presentation, or large birth weight.…”
Section: Introductionmentioning
confidence: 99%
“…Only one case of the 14 FAH that persisted postnatally (7.1%, Table 2) was managed conservatively 3 . Three of the 22 cases with “regression or decrease in size” on postnatal imaging underwent surgery 30,32,35 . One case was followed up for 2 months 35 prior to surgical intervention.…”
Section: Resultsmentioning
confidence: 99%
“…An adrenal gland damaged by hemorrhage, or the removal of one or both glands, can result in adrenal insufficiency, which presents with seizures, hypoglycemia, hypotension, and hyponatremia. 24 When adrenal insufficiency occurs, replacement therapy is necessary to avoid the serious complications associated with this condition. A late complication of adrenal hemorrhage is hypertension.…”
Section: Adrenal Hemorrhagementioning
confidence: 99%